Differentiation with Raman spectroscopy among several natural ultramarine blues and the synthetic ultramarine blue used by the Catalonian modernist painter Ramon Casas i Carbó1. (10th November 2014) - De Torres, A. R.; Ruiz‐Moreno, S.; López‐Gil, A.; Ferrer, P.; Chillón, M. C.; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> This paper investigates, using only Raman spectroscopy, the spectral differences among the synthetic ultramarine blue (J. B. Guimet) and three natural ultramarine blues (lazurites) corresponding to three lapis lazulis from different geographical sources (Chile, Afghanistan and Siberia). The synthetic ultramarine blue used as reference pigment is the identified in an artwork created around 1917 by the Catalonian modernist painter Ramon Casas i Carbó. This synthetic pigment is compared with the three natural ultramarine blues and, in his turn, the latter are also compared each other. In order to quantify the spectral differences, a rigorous methodology based on the Euclidean distance between homologue spectral segments (or intervals) has been developed and presented here. Copyright © 2014 John Wiley & Sons, Ltd.